The lost art of Khmer classical dance - Hem, Paulina (Special Collections & Archives, University of Waterloo Libraries, 2019)
Once upon a time, SCA used to collect items for the University’s Dance program. Many of these items are part of the Henry H. Crapo collection. A part of the collection were books on the histories of dances from all over the world, including traditional Indochinese (what is now Southeast Asia) dances. It was an exciting surprise to find books on classic Cambodian dances or Robam Kbach Boran. As a young Cambodian-Canadian child growing up in the Waterloo Region, there weren’t exactly many books about Cambodia lying around. The rare books I found in the collection dated back to the early 20th century. It was a time before the Khmer Rouge, and the Royal Ballet of Cambodia troupe was still flourishing. Under the genocidal regime of the Khmer Rouge, the Royal Ballet of Cambodia lost almost “90 percent of its members due to execution, malnutrition, and forced labour". With them, many of the teachings and traditional ways of Robam Kbach Boran were lost.
Keywords: SCA blog; Khmer classical dance